Protein quantitative trait locus study in obesity during weight-loss identifies a leptin regulator - Jérôme Carayol (Nature Portfolio, 2017)
Although many genetic variants are known for obesity, their function remains largely unknown. Here, in a weight-loss intervention cohort, the authors identify protein quantitative trait loci associated with BMI at baseline and after weight loss and find FAM46A to be a regulator of leptin in adipocytes.